TEACHERS’ PERFORMANCE IN ONLINE LEARNING DURING COVID-19 OUTBREAK: AN ANALYSIS BASED ON 21st CENTURY PROFICIENCY - Ayub, Daeng; Adi Putra, M. Jaya (International Journal of Educational Best Practices, 2021)
The pandemic phenomenon has forced the world of education to change the work pattern of services from conventional to online-based education and learning services. This study aimed to describe and analyze the level of teachers’ 21st century proficiency and its effect on teachers’ performance in online learning due to Covic-19. This research was conducted at the Alkautsar Integrated Islamic Education Foundation School, with a population of 90 teachers and a sample of 68 teachers. This is a descriptive quantitative research conducted by a survey design. The main tool for data collection is a questionnaire. Data were analyzed using descriptive statistics by calculating the mean value of teachers' 21st century competence and teachers’ performance in online learning due to Covic-19. Inferential statistical analysis was also carried out to find the magnitude of the relationship and influence between variables. The results showed that the average score of level of teachers’ performance in online learning was 3.56 in the high category. The 21st century proficiency level of teachers with a mean value of 3.72 was also in the high category. It was also found that there is a significant relationship between 21st century proficiency variables and teachers’ performance in online learning of 0.809. The effect of 21st century skills on teachers’ performance in online learning was 65.50%. The conclusion is that the better the 21st century skills of teachers, the better the teacher's performance in online learning due to Covid-19.